Outcomes of attention-related communication deficits following traumatic brain injury: perspectives of international health professionals. (23rd February 2022) - VanSolkema, Maegan; McCann, Clare M.; Barker-Collo, Suzanne; Foster, Allison
ABSTRACT: Primary Objective: Attention and communication difficulties are common yet often invisible following Traumatic Brain Injury (TBI). The focus of this paper is to use practice-based evidence from health professionals working with individuals following TBI to gain a deep and relevant understanding of the impact that attention and communication can have in the lives of individuals following TBI. Research Design: This dataset comes from a larger mixed-methods study that includes a survey with both open and closed questions and focus group data sources. Methods and Procedures: Thematic analysis was completed on a single open-ended question from the survey of health professionals. It asked health professionals about the outcomes they believe are directly related to attention difficulties that result in specific communication difficulties. Main Outcomes and Results: Responses from 73 health professionals who work in neurorehabilitation generated five themes: behavior, connections, self, purpose, and empowerment. The themes were pervasive across all aspects of the recovery journey for individuals post-TBI Conclusions: The implications for clinical practice and future research indicate a need to focus on attention-related strategies for language deficits; treating communication difficulties related to relationships and friendships; and redefining a sense of self following TBI.